Healthy Antenatal Risk-monitoring (HARMONY) Effectiveness of Volunteer Assistance Using a Booklet on Improving Risk Detection During Pregnancy - Indriani, Ririn; Susiloretni, Kun A; wahyuni, sri; Abiddin, Andi Hayyun (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2025)
Early identification of pregnancy risk factors using the Maternal and Child Health (MCH) handbook and the Poedji Rochyati Score Card can be carried out by pregnant women or community health volunteers (cadres). Supporting cadres in identifying high-risk pregnancies facilitates timely detection and appropriate intervention. This study aimed to develop a pregnancy risk detection booklet based on the MCH handbook. A cluster randomized controlled trial with a pretest-posttest control group design was conducted in eight villages, involving 30 selected cadres recommended by local midwives based on their active participation. The intervention group received training and assistance using the developed booklet. The results demonstrated that cadres in the intervention group had significantly greater improvement in pregnancy risk detection skills compared to the control group, with a mean difference of 18.7 (95% CI: 15.2–22.2, p=0.001). In addition, cadre performance in antenatal care using the 10T approach improved by 15.7% (95% CI: 11.3–20.1, p=0.001) in the intervention group relative to the control. These findings suggest that the booklet is an effective tool for enhancing cadres’ competencies in early pregnancy risk screening and service delivery. Further development of the booklet with more engaging and culturally relevant content may enhance its utility and adoption in community health settings.